PENCEGAHAN PENULARAN TUBERKULOSIS PADA BALITA DI DESA TRANGSAN KECAMATAN GATAK KABUPATEN SUKOHARJO JAWA TENGAH - Maryani Setyowati; Noor Alis Setiyadi (Universitas Muhammadiyah Surakarta, 2025)
Tuberculosis (TB) remains a major public health problem in Indonesia, including in Sukoharjo Regency. In 2022, the TB case detection rate in this area reached only 54.5% of the established target. TB causes significant impacts not only on health but also on social and economic aspects; therefore, comprehensive prevention and control efforts involving multiple stakeholders are essential. Adolescents and families, particularly mothers of toddlers, play an important role in preventing TB transmission through improved knowledge and healthy behaviors. Limited access to health information may lead to low levels of knowledge and increase the risk of TB transmission in the community. This community service activity aimed to increase knowledge about tuberculosis transmission among mothers of toddlers in Trangsan Village, Sukoharjo Regency. The activity involved 26 participants and was conducted offline through health education sessions and interactive discussions. Knowledge evaluation was carried out using pre-test and post-test assessments. The results showed an improvement in participants’ knowledge, as indicated by an increase in the average post-test score (8.9) compared to the pre-test score (7). These findings demonstrate that health education is effective in improving community knowledge regarding tuberculosis. Therefore, sustained commitment and collaboration among the community, primary healthcare centers, and the Sukoharjo Regency Health Office are necessary to ensure optimal implementation of TB prevention and control programs.